2008
DOI: 10.1186/1752-1505-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Antismoking messages and current cigarette smoking status in Somaliland: results from the Global Youth Tobacco Survey 2004

Abstract: BackgroundTobacco is a leading cause of death globally. There are limited reports on current cigarette smoking prevalence and its associated-antismoking messages among adolescents in conflict zones of the world. We, therefore, conducted secondary analysis of data to estimate the prevalence of current cigarette smoking, and to determine associations of antismoking messages with smoking status.MethodsWe used data from the Somaliland Global Youth Tobacco Survey (GYTS) of 2004 to estimate the prevalence of smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…While previous reports have suggested that exposure to tobacco advertisements [14][15][16][17] through the media, having ever been offered a free cigarette and possessing an item with a cigarette brand logo on it were associated with smoking, we found that adolescents in Zambia seemed to behave differently. While this study was not designed to answer why this may have been the case, there are possible explanations.…”
Section: Discussioncontrasting
confidence: 53%
“…While previous reports have suggested that exposure to tobacco advertisements [14][15][16][17] through the media, having ever been offered a free cigarette and possessing an item with a cigarette brand logo on it were associated with smoking, we found that adolescents in Zambia seemed to behave differently. While this study was not designed to answer why this may have been the case, there are possible explanations.…”
Section: Discussioncontrasting
confidence: 53%
“…For adolescents, the prevalence of smoking ranged from 2.2% for IDP adolescents in northern Uganda56 to around 70% for Israeli youth 43. When stratified by gender, male smoking prevalence ranged from 10.3% among Somaliland youths61 to 70.7% among Serbian adults during war;62 and female smoking prevalence ranged from 0.6% among Palestinian refugees in Gaza54 to 70% among female Israeli youths 43…”
Section: Patterns Of Tobacco Usementioning
confidence: 99%
“…Thirteen studies found significant association between male gender and higher tobacco use 28 34 37 40 44 45 52 54 55 58 60 62 64. Four studies found no statistical significance between gender and tobacco use,29 56 61 including one looking at the association between gender and nicotine dependence among Bosnian refugees in the USA 65. A study on Israelis youths found significant association between higher cigarette use and female gender 43.…”
Section: Patterns Of Tobacco Usementioning
confidence: 99%
See 1 more Smart Citation
“…This association between pro-tobacco advertising or promotion and cigarette use has been confirmed in several studies (e.g., Siziya et al, 2007;Shah, Pednekar, Gupta, & Sinha, 2008;ineZulu, Siziya, Muula & Rudatsikira, 2009). Exposure to counter-marketing and school and family anti-smoking education have been found in some studies to be protective from smoking (Koh et al, 2011;Siziya et al, 2008a;.…”
mentioning
confidence: 97%